2021
DOI: 10.3389/fpubh.2021.709410
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Substance Use and Its Relationship to Stress, Emotional State, Depressive Symptomatology, and Perceived Threat During the COVID-19 Pandemic in Mexico

Abstract: People can increase their use of psychoactive substances in response to stressful situations as a maladaptive mechanism for reducing negative affective states. It is therefore necessary to examine changes in the use of such substances and their relationship to mental health in light of the COVID-19 pandemic.Objective: Evaluate the relationship between psychoactive substances and stress, emotional state, and symptomatology during the COVID-19 lockdown in Mexico.Method: A national survey was conducted, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
(50 reference statements)
3
14
0
1
Order By: Relevance
“…Our findings largely parallel results from existing online surveys of alcohol consumption during the COVID-19 pandemic, suggesting stronger declines in drinking in Colombia [ 18 ] than in Mexico [ 19 ] (for an international review of studies, see eg, [ 20 ]). As a key driver for reduced alcohol consumption during the pandemic, restrictions to social gatherings have been suggested, both in terms of closed bars, venues and events and acceptable social contact with colleagues, friends and family [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings largely parallel results from existing online surveys of alcohol consumption during the COVID-19 pandemic, suggesting stronger declines in drinking in Colombia [ 18 ] than in Mexico [ 19 ] (for an international review of studies, see eg, [ 20 ]). As a key driver for reduced alcohol consumption during the pandemic, restrictions to social gatherings have been suggested, both in terms of closed bars, venues and events and acceptable social contact with colleagues, friends and family [ 21 ].…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the segment and gender, only the technicians and the male audience did not present a worsening in the aspects of quality of life associated with the increase in alcohol and/or marijuana consumption; the women, in turn, had a higher frequency of worsening in quality of life and psychosocial aspects associated with increased alcohol use compared to men. Several studies show statistical similarities between increased alcohol consumption among men and women—in this study, as previously discussed, the percentage of women who increased their use of alcohol was higher than that of men—but men used to have the highest rates (Andrade, Duarte & Oliveira, 2010; Fundação Oswaldo Cruz (Fiocruz), 2020 ; Martínez-Vélez et al, 2021 ; Tavolacci et al, 2016 ; Terra Junior et al, 2021;). A higher frequency of worsening in quality of life and psychosocial aspects associated with increased alcohol use among women agreeing with other studies (Barros et al, 2022 ; Eleftheriou et al, 2021 ; Herrera-Añazco et al, 2022 ; Johnson et al, 2020 ) and it may be associated with various dynamics linked to gender roles.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies reported the increasing occurrence of mental health disorders such as stress, depression, and anxiety during SD (Bhattacharjee & Acharya, 2020 ; Hossain et al, 2020 ; Huang & Zhao, 2020 ). The scientific literature also reveals that alcohol and other drug use during SD may be related to the incidence of these mental health disorders (Gavurova et al, 2020 ; Martínez-Vélez et al, 2021 ) , as well as negatively impacting the quality of life—defined as an individual’s perception of his/her position in life in the context of the culture in which he/she lives and regarding his/her goals, expectations, standards, and concerns (World Health Organization, 1995 ).…”
mentioning
confidence: 99%
“…Tranquilizer use was associated with most of the mental health outcomes, and to our knowledge, no other study has explored this specific association among undergraduates during the pandemic. We only found one study in Mexico among the general population where they found that tranquilizer use increased the levels of stress and depressive symptomatology ( 68 ). On the other hand, we found that alcohol use was associated with a reduced risk for depressive symptoms and suicide risk.…”
Section: Discussionmentioning
confidence: 99%